Media Relation On Branding Activity Of Muhammadiyah University Of Prof. Dr. Hamka With Peso Model Study - sulis, Sulis; Kuswanti, Ana (Universitas 17 Agustus 1945 Surabaya, 2024)
Public relations (PR) has an important role for higher education. The implementation of PR strategies is expected to create a positive image that attracts public attention while achieving institutional goals. One of them is by utilising media relations in branding activities. PR measures the mutually beneficial relationship between an organisation and its main public. It is also related to reputation management and crisis communication. According to the International Public Relations Association (IPRA, 1978). The formulation of the problem in this research is how the media relations strategy in university branding activities through the PESO Model study. While the purpose of this research is to describe and explain the strategy of University Public Relations, especially Uhamka Public Relations in establishing media relations through the PESO Model view. So as to obtain the benefits of this research, academically the research is useful for developing PESO Model studies on media relations activities carried out by Uhamka. The practical benefit is that Public Relations at the University can use the PESO Model strategy so that it can improve branding at the University.